Oxidative stress in testicular tissues of rats exposed to cigarette smoke and protective effects of caffeic acid phenethyl ester - Ozyurt, H; Pekmez, H; Parlaktas, BS; Kus, I; Ozyurt, B; Sarsilmaz, M (Wolters Kluwer Medknow Publications, 2006)
Aim: To show the oxidative stress after cigarette smoke exposure in rat testis and to evaluate the effects of caffeic acid phenethyl ester (CAPE). Methods: Twenty-one rats were divided into three groups of seven. Animals in Group I were used as control. Rats in Group II were exposed to cigarette smoke only (4 x 30 min/d) and rats in Group III were exposed to cigarette smoke and received daily intraperitoneal injections of CAPE (10 mu mol/kg-d). After 60 days all the rats were killed and the levels of nitric oxide (NO) and anti-oxidant enzymes such as superoxide-dismutase, catalase and glutathione peroxidase (GSH-Px) and the level of malondialdehyde were studied in the testicular tissues of rats with spectrophotometric analysis. Results: There was a significant increase in catalase and superoxide-dismutase activities in Group II when compared to the controls, but the levels of both decreased after CAPE administration in Group III. GSH-Px activity was decreased in Group II but CAPE caused an elevation in GSH-Px activity in Group III. The difference between the levels of GSH-Px in Group I and Group II was significant, but the difference between groups II and III was not significant. Elevation of malondialdehyde after smoke exposure was significant and CAPE caused a decrease to a level which was not statistically different to the control group. A significantly increased level of NO after exposure to smoke was reversed by CAPE administration and the difference between NO levels in groups I and III was statistically insignificant. Conclusion: Exposure to cigarette smoke causes changes in the oxidative enzyme levels in rat testis, but CAPE can reverse these harmful effects.
Keywords: testis; cigarette; caffeic acid phenetyl ester; anti-oxidants; nitric oxide